Comparison of antimicrobial resistance and DNA patterns of Salmonella Schwarzengrund isolated from human and chicken meat in Thailand - Jharuwan Pansung (Chulalongkorn University, 2012)
Thesis (M.Sc.)--Chulalongkorn University, 2004